2015
DOI: 10.1002/pmic.201400627
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring matrix metalloproteinase activity at the epidermal–dermal interface by SILAC‐iTRAQ‐TAILS

Abstract: Secreted proteases act on interstitial tissue secretomes released from multiple cell types. Thus, substrate proteins might be part of higher molecular complexes constituted by many proteins with diverse and potentially unknown cellular origin. In cell culture, these may be reconstituted by mixing native secretomes from different cell types prior to incubation with a test protease. Although current degradomics techniques could identify novel substrate proteins in these complexes, all information on the cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…A combined approach of iTRAQ-based terminal amine isotopic labeling of substrates (iTRAQ-TAILS) with SILAC was utilised by Keller and colleagues to assign proteins to a specific cell type by MS1-and their cleavage by MS2-based quantification in the same experiment. By using this hybrid technique they investigated the matrix metalloproteinase MMP10-dependent processing of extracellular proteins derived from either keratinocyte or fibroblast secretomes to give insight into processing of proteins such as collagens and laminins at the dermal epidermal interface [92]. In a subsequent study the same group applied the same methodology and identified integrin α6, cysteine-rich angiogenic inducer 61 and dermokine as novel MMP10…”
Section: Degradomicsmentioning
confidence: 99%
“…A combined approach of iTRAQ-based terminal amine isotopic labeling of substrates (iTRAQ-TAILS) with SILAC was utilised by Keller and colleagues to assign proteins to a specific cell type by MS1-and their cleavage by MS2-based quantification in the same experiment. By using this hybrid technique they investigated the matrix metalloproteinase MMP10-dependent processing of extracellular proteins derived from either keratinocyte or fibroblast secretomes to give insight into processing of proteins such as collagens and laminins at the dermal epidermal interface [92]. In a subsequent study the same group applied the same methodology and identified integrin α6, cysteine-rich angiogenic inducer 61 and dermokine as novel MMP10…”
Section: Degradomicsmentioning
confidence: 99%
“…A major challenge is the low concentration of secreted proteins within the conditioned medium (Schira-Heinen et al, 2019). Therefore, many studies concentrate medium from tens of millions of cells (Kleifeld et al, 2010(Kleifeld et al, , 2011Kuhn et al, 2012;Wiita et al, 2014;Schlage et al, 2015). However, such numbers are often not available for primary cells, such as microglia, where on average one million cells may be purified from the brain of individual adult mice.…”
Section: Introductionmentioning
confidence: 99%
“…[34] While the present review focuses on inhibitors of MMP-2, MMP-9, MMP-13, MT1-MMP, ADAM8, ADAM10, and ADAM17 (see below), and hence our proteomics discussion addresses these proteases, proteomic analyses of the degradomes of other MMPs, such as MMP-10 and MMP-12, have been reported. [35][36][37][38] In addition, proteomic identification of protease cleavage sites (PICS) has evaluated the cleavage site preferences for (a) Nine MMP family members in trypsin-and GluC-generated human whole-proteome peptide libraries [39,40] and (b) ADAM10 and ADAM17 in LysC-and GluC-generated yeast whole proteome peptide libraries. [41] Activity-based protein profiling (ABPP) probes have been used to document metalloproteinases up-regulated in invasive cancer cells.…”
Section: Proteomic Profiling Of Mmp and Adam Activitymentioning
confidence: 99%